INDONES J MED 2016
DOI: 10.26911/theijmed.2017.02.01.06
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Gestational Biological, Social, Economic Factors on Undernutrition in Infants 6-12 Months in Cilacap

Abstract: Background: Undernutrition in children under five can cause disorder in the physical growth, mental development, low intellegence, or even death. This study aimed to test the hypothesis that under nutrition in infants aged 6-12 months is associated with gestational biological, social, and economic factors. Subjects and Method: This was an analytic and observational study with case control design. This study was conducted in Cilacap, Central Java. A total of 144 infants aged 6-12 months were selected by fixed d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 12 publications
1
1
0
5
Order By: Relevance
“…High maternal education cannot mean that mothers have a good knowledge in the fulfillment of child nutrition. This is in accordance with research conducted by M. Septikasari (2016) where in her research showed no significant relationship between maternal education level with child nutrition status. [18] Education on the one hand has a positive impact that the mother increasingly understands the importance of health care.…”
Section: Discussionsupporting
confidence: 92%
“…High maternal education cannot mean that mothers have a good knowledge in the fulfillment of child nutrition. This is in accordance with research conducted by M. Septikasari (2016) where in her research showed no significant relationship between maternal education level with child nutrition status. [18] Education on the one hand has a positive impact that the mother increasingly understands the importance of health care.…”
Section: Discussionsupporting
confidence: 92%
“…Hasil penelitian ini sejalan dengan penelitian Case Control yang dilakukan di Kelurahan Sangkrah, Surakarta bahwa sebanyak 70% kelompok kasus tidak memiliki riwayat BBLR, tetapi hasil penelitian tersebut menyatakan ada hubungan yang bermakna antara berat lahir dengan kejadian stunting pada balita (OR=12,429; p=0,006) (6). Penelitian lain yang juga memberikan hasil serupa adalah penelitian yang dilakukan oleh Septikasari di Cilacap yang menyatakan bahwa anak yang dilahirkan dengan berat badan yang rendah berpeluang untuk mengalami kekurangan gizi sebesar delapan kali lebih besar dibandingkan yang dilahirkan dengan berat normal, serta diketahui kejadian BBLR merupakan salah satu faktor prediktor dari kekurangan gizi pada balita di Cilacap (OR=8,12; 95%CI=0,92-71,64) (15). Bayi yang dilahirkan dengan berat badan normal akan cenderung memiliki pertahanan diri yang lebih baik untuk tidak mengalami stunting dibandingkan dengan bayi yang BBLR (OR=1,85; 95%CI=1,282-2,662) (16).…”
Section: Stuntingunclassified
“…Hal tersebut yang menyebabkan anak dengan BBLR memiliki pertumbuhan dan perkembangan yang lebih lambat. Selain itu, anak yang BBLR lebih rentan mengalami penyakit infeksi jika asupan gizi tidak diupayakan secara optimal dan tidak terjamin hygiene sanitasinya sehingga anak lebih berisiko mengalami permasalahan gizi seperti stunting (15).…”
Section: Stuntingunclassified
“…Pemberian ASI saja sampai bayi berusia 6 bulan atau disebut ASI eksklusif mampu memenuhi seluruh kebutuhan nutrisi bayi. Selain mampu memenuhi kebutuhan nutrisi bayi, ASI eksklusif juga bermanfaat dalam meningkatkan kecerdasan anak (Septikasari, Akhyar, & Wiboworini, 2016). Aspek fungsi kognitif pada bayi yang di beri ASI eksklusif memberikan hasil lebih baik dibanding dengan yang tidak mendapat ASI eksklusif (Novita, Gurnida, & Garna, 2008).…”
Section: Pendahuluanunclassified